Nonlinear Dynamic Analysis of Turbocharger Flexible Rotor System Supported on Floating Ring Bearings - Singh, Ajit; Gupta, T. C. (Journal of Applied Nonlinear Dynamics, 2026)
In the present research work, the Timoshenko beam element theory has been used to develop the finite element model of the turbocharger rotor system. The nonlinear fluid film forces generated in floating ring bearings have been derived. A new MATLAB code has been constructed using Newmark-β numerical integration scheme along with Newton-Raphson method to solve the equations of motion of the system. The orbital plots, Poincaremaps, and time response plots are obtained at different nodes, for various speeds to study the nonlinear dynamic behavior of floating ring bearings and turbocharger rotor system.